Retinal ganglion cell/inner plexiform layer thickness in patients with Parkinson’s disease - Živković, Maja; Dayanir, Volkan; Stamenović, Jelena; Ljubisavljević, Srdjan; Pražić, Ana; Zlatanović, Marko; Zlatanović, Gordana; Jakšić, Vesna; Radenković, Marija; Jovanović, Svetlana (Folia Neuropathologica, 2017)
Introduction: The aim of the paper was to analyze the changes in the macular ganglion cell layer and inner plexiform layer (GCL-IPL) thickness in patients with Parkinson’s disease. Material and methods : The study enrolled 46 patients with established diagnosis of Parkinson’s disease and 46 healthy subjects. Both groups were age- and gender-matched. An OCT protocol, namely standardized Ganglion Cell Analysis algorithm was used to measure the thickness of the macular GCL-IPL layer. The average, minimum, and six sectoral (superotemporal, superior, superonasal, inferonasal, inferior, inferotemporal) GCL-IPL thicknesses were measured from the elliptical annulus centered on the fovea. Results : The mean value of the clinical severity of Parkinson’s disease was between 2 and 3, according to the Hoehn and Yahr scale. Statistically significant thinning of the GCL-IPL layer was registered in average and minimum GCL-IPL thickness, as well as in the sectoral layer thicknesses in patients with Parkinson’s disease in comparison to the controls. There was no correlation between structural changes in the retina and disease duration or severity. A statistically significant difference in thickness between the different stages of the disease was registered only in the inferior sector. Conclusions : Parkinson’s disease is accompanied by thinning of the GCL-IPL complex of macula even in the earliest stages. This may indicate a possible retinal dopaminergic neurodegeneration. There is no correlation between duration or severity of Parkinson’s disease with thinning of the GCL-IPL complex.